Rural Self-employment Programmes in India – A Review - S. Santhosh Kumar and Helaney M.Y (Commerce Spectrum, 2014)
Rural unemployment is still an unresolved social problem demanding remedy. Erstwhile self- employment and wage employment programmes were alleged to be underprovided in bringing down the unemployment rate as planned. Irrespective of the number of programmes, effective employment generation through different programmes is important. The paper reviews the self- employment programmes implemented in the country since the Sixth Five-year Plan period.